UPAYA PENINGKATAN MOTIVASI DAN HASIL BELAJAR AKUNTANSI MELALUI PENGGUNAAN BAHAN AJAR BROSUR SISWA KELAS X AKUNTANSI SMK SURAKARTA - Perdanasari, Ayu; Santoso, Sigit; Octoria, Dini (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThis research aims to improve the motivation and accounting learning outcomes through the use of brochure as learning materials for 10 grade students of accounting in SMK Surakarta. This research is a classroom action research conducted in two cycles, with research procedure: (1) planning, (2) ac-tion implementation, (3) observation, and (4) reflection. The subjects of the research were 10 grade stu-dents of accounting, amounted to 46 students. Source of data comes from informants and documents. Data collection for students learning motivation is done by observation, interview and questionnaires, while for the data collecting of students learning outcome is done by test technique. The validity of data using technique triangulation method. Data analysis uses descriptive statistics and interactive models. Performance indicators of this research were set at 85%. The results of this research indicate that the use of brochure learning materials can improve motivation and accounting learning outcomes. Learn-ing motivation is known from the result of questionnaire equal to 77,57% and observation equal to 74,22%, in cycle II the result of questionnaire equal to 88,04% and observation equal to 86,78%. The increase of learning outcomes is known from the achievement in cycle I to 57,78% and in cycle II to 86,67%.Keywords: learning material, brochure, motivation, accountingABSTRAKPenelitian ini bertujuan untuk meningkatkan motivasi dan hasil belajar akuntansi melalui penggunaan bahan ajar brosur siswa kelas X Akuntansi SMK Surakarta. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus, dengan prosedur penelitian: (1) perencanaan, (2) pelaksanaan tindakan, (3) observasi, dan (4) refleksi. Subjek penelitian adalah siswa kelas X Akuntansi yang berjumlah 46 siswa. Sumber data berasal dari informan dan dokumen. Pengum-pulan data untuk motivasi belajar siswa dilakukan dengan teknik observasi, wawancara dan angket, se-dangkan untuk pengumpulan data hasil belajar siswa dilakukan dengan teknik tes. Validitas data menggunakan teknik triangulasi metode. Analisis data menggunakan statistik deskriptif dan model inter-aktif. Indikator kinerja penelitian ditetapkan sebesar 85%. Hasil penelitian ini menunjukkan bahwa penggunaan bahan ajar brosur dapat meningkatkan motivasi dan hasil belajar akuntansi. Motivasi belajar siswa pada siklus I diketahui dari hasil angket sebesar 77,57% dan observasi sebesar 74,22%, pada siklus II angket sebesar 88,04% dan observasi sebesar 86,78%. Peningkatan hasil belajar diketahui dari capaian pada siklus I sebesar 57,78% dan pada siklus II sebesar 86,67%.Kata Kunci: bahan ajar, brosur, motivasi, akuntansi